Project Approach; A Way How To Trigger Children Expose And Explore Their Skills In Learning A Language - Jumbuh Prabowo (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract: Teaching English for young learners always gets more attention. It is because young learners are very unique. They have many characters which can change rapidly in one time. Sometimes, they display an enthusiasm for learning and a curiosity about the world around them. They also have a need for individual attention and approval from the teacher. They are keen to talk about themselves, and respond well to learning that uses themselves and their own lives as main topics in the classroom. However, they also have a limited attention span. They can easily get bored, losing interest after ten minutes if the activities are not extremely engaging. For overcoming this situation, teachers need to choose an approach that can invite the students to be more active. One of the suitable approaches is project approach (hereafter PA). Katz & Chard (1989) define that a project is an extended study of a topic usually undertaken by a group of children, sometimes by a whole class, and occasionally by an individual child. Applying PA in teaching learning process can be used to maximize the skills in Bloom Taxonomy. Key words: Pelajar Muda, Karakter, Perhatian, Pendekatan Proyek.